2019
DOI: 10.4162/nrp.2019.13.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D intake and bone mineral density in Koreans aged ≥ 50 years: analysis of the 2009 Korea National Health and Nutrition Examination Survey using a newly established vitamin D database

Abstract: BACKGROUND/OBJECTIVES Vitamin D plays an important role in skeletal growth and maintenance and in the prevention of various diseases. We investigated the relationship between vitamin D intake and bone mineral density (BMD) in Korean adults aged ≥ 50 years using the 2009 Korea National Health and Nutrition Examination Survey data. SUBJECTS/METHODS This study was conducted in 1,808 subjects aged ≥ 50 years with BMD data in Korea. Dietary vitamin D levels were assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…We speculate that higher serum vitamin D levels observed in the middle and high eCRF groups compared with the low eCRF group may be due to group differences in body fat [36] or nutritional intake [37] or outdoor activity [38,39]. In particular, the importance of the nutritional intake of vitamins D and B and calcium in relation to bone health was previously reported from recent studies using a nationwide survey data [6,37].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We speculate that higher serum vitamin D levels observed in the middle and high eCRF groups compared with the low eCRF group may be due to group differences in body fat [36] or nutritional intake [37] or outdoor activity [38,39]. In particular, the importance of the nutritional intake of vitamins D and B and calcium in relation to bone health was previously reported from recent studies using a nationwide survey data [6,37].…”
Section: Discussionmentioning
confidence: 74%
“…With a rapidly rising elderly population, osteoporosis has become a serious public health issue in both developed and developing countries [2]. The prevalence of osteoporosis is also associated with behavioral risk factors such as smoking, heavy alcohol consumption [3], dietary intake [4,5], vitamin D deficiency [6], and physical inactivity [7] in conjunction with low socio-economic status [8].…”
Section: Introductionmentioning
confidence: 99%
“…We observed that vitamin D and calcium supplementation affected BMD but not serum 25(OH)D, calcium and iPTH levels, as vitamin D is an essential vitamin to maintain PTH levels to stabilize serum calcium [48,49]. It has been reported that increased vitamin D and/ or calcium intakes have been associated with a positive correlation with BMD despite the normal calcium levels which are controlled by several factors, such as serum albumin and acid‐base status [50].…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted to determine the vitamin D intake in Korean adults using the 2009–2011 KNHANES and the vitamin D food database established in our laboratory [ 13 21 24 ], and its relationship to serum 25(OH)D or BMD. Although the data for each year were analyzed in our previous study, the relationship between vitamin D intake and BMD and serum levels of vitamin D was not established due to the exclusion of large number of participants who did not meet the study criteria.…”
Section: Discussionmentioning
confidence: 99%